ON SPECTRAL PROPERTIES OF A NEW OPERATOR OVER SEQUENCE SPACES c AND c(0) - (:unkn) unknown (SPRINGER, 2014)
In this work, we classify and calculate spectra such as point spectrum, continuous spectrum and residual spectrum over sequences spaces l(infinity), c and c(0) according to a new matrix operator W which is obtained by matrix product.
Keywords: spectrum of an operator; matrix transformation; sequence space; DIFFERENCE OPERATOR; FINE SPECTRUM; BV(P); DELTA; L(P)